HIV Susceptibility of human antigen-specific CD4 T cells in AIDS pathogenesis and vaccine response. (2nd June 2016) - Hu, Haitao; Liu, Fengliang; Kim, Jerome; Ratto-Kim, Silvia
ABSTRACT: HIV causes infection and progressive depletion of human CD4 T cells. Emerging data have shown that antigen-specific CD4 T-cell subsets manifest differential susceptibility to HIV, potentially leading to pathogen-specific immune failure and opportunistic infections. This concept was recently explored in context of vectors utilized in HIV vaccine trials, and the data suggest that adenovirus type 5(Ad5)-specific CD4 T cells elicited by Ad5-HIV vaccine may be particularly susceptible to HIV, potentially rendering Ad5 vaccine recipients susceptible to HIV acquisition. We here examined recent data regarding the HIV susceptibility of antigen-specific CD4 T cells induced during infection or HIV vaccination and discussed its potential impact on HIV acquisition risk posed by HIV vaccination.